Dojrzała twórczość Józefa Pankiewicza z lat 1919–1940 – wybrane aspekty warsztatowe - Wachowiak, Mirosław (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2013)
The paper summarises technical and technological issues of the last period of the Pankiewicz art after his return from Spain to France in 1919 till his death in 1940. it presents reworking colouristic experiments of the Spanish period and relating them to more ordered vision in works from the 19201921, and later on leaving rich colours for the reason of stressing more classical solutions in the late 1920-ies. Then the drawing and construction is growing in importance, brown underpaintings are used and the palette is significantly narrowed. Parallel there exists two streams –organic and rich in colour and texture as well as more classical, modest, in broken and darkened hues and matt paint-layer surface. In the 1930-ies the artist summarises earlier experiences and connect in one vision respect for the nature and Old Masters with decorative understanding of the image proposed by Impressionists, Cezanne, Bonnard. Observation of the evolution of the technique is supported with the results of technological analyses, especially of XRF executed in non – invasive way in situ using portable spectrometer.